An Examination of Medical Malpractice Claims Involving Physician Trainees. (August 2020) - Myers, Laura C.; Gartland, Rajshri M.; Skillings, Jillian; Heard, Lisa; Bittner, Edward A.; Einbinder, Jonathan; Metlay, Joshua P.; Mort, Elizabeth
Abstract : Purpose: To identify patient-, provider-, and claim-related factors of medical malpractice claims in which physician trainees were directly involved in the harm events. Method: The authors performed a case–control study using medical malpractice claims closed between 2012–2016 and contributed to the Comparative Benchmarking System database by teaching hospitals. Using the service extender flag, they classified claims as cases if physician trainees were directly involved in the harm events. They classified claims as controls if they were from the same facilities, but trainees were not directly involved in the harm events. They performed multivariable regression with predictor variables being patient and provider characteristics. The outcome was physician trainee involvement in harm events. Results: From the original pool of 30, 973 claims, there were 581 cases and 2, 610 controls. The majority of cases involved residents (471, 81%). Cases had a statistically significant higher rate of having a trainee named as defendants than controls (184, 32% vs 233, 9%; P < .001). The most common final diagnosis for cases was puncture or laceration during surgery (62, 11%). Inadequate supervision was a contributing factor in 140 (24%) cases overall, with the majority (104, 74%) of these claims being procedure related. Multivariable regression analysis revealed that trainees were most likely to be involved in harm events in specialties such as oral surgery/dentistry and obstetrics–gynecology (OR = 7.99, 95% CI 2.93, 21.83 and OR = 1.85, 95% CI 1.24, 2.66, respectively), when performing procedures (OR = 1.58, 95% CI 1.27, 1.96), or when delivering care in the emergency room (OR = 1.65, 95% CI 1.43, 1.91). Conclusions: Among claims involving physician trainees, procedures were common and often associated with inadequate supervision. Training directors of surgical specialties can use this information to improve resident supervision policies. The goal is to reduce the likelihood of future harm events. Abstract : Supplemental Digital Content is available in the text.